Site responsivo de aptidão física relacionada com a saúde para adultos aparentemente saudáveis. - Schuindt da Silva, Vladimir; Neivor Dornelles, Thauan; Eduardo Seisl, Sigfried; Matteucci Júnior, Alceu; Márcia da Rocha, Tatiana; Souza, Israel (Caderno de Educação Física e Esporte, 2022)
OBJECTIVE: To describe the process of development, the main features and applicability of a responsive website to assess/improve the Health-Related Physical Fitness (HRPF) of apparently healthy adults. METHODS: Methodological study, conducted in four stages: functional requirements elicitation with two Physical Education teachers, a Bachelor's degree in Nutrition and three IT technicians (access and tools based on scientific evidence to HRPF) and non-functional requirements (development: Bootstrap 4 framework; programming languages: HTML5, CSS3, PHP 7.4.0 and Javascript; database manager: SQLite; running by browsers: Google Chrome, Mozilla Firefox and Internet Explorer); prototyping by the IT team; testing (design; usability; language; instructions; security; and transfer) by 31 participants, selected for convenience, with a mean age of 30.5 years (17 women); and implementation of the responsive website, hosted on the server of a Federal Institute (FI) in the midwest region of Santa Catarina, Brazil, with free access to use, without specific login and password required. The frequency and percentage of the items in the evaluation criteria were calculated. Data were tabulated in Microsoft Excel®. RESULTS: The responsive site was evaluated as having a satisfactory design, easy to use, with instructions ratings of medium to good, moderate security, and for transfer to other devices, predominantly, neither easy nor difficult. CONCLUSION: It was possible to verify that the functional characteristics of the responsive site present interactive content, in a facilitated way, that can contribute to the improvement or maintenance of good levels of HRPF, as well as the evaluation of its components, based on scientific evidence, of apparently healthy adults.